Clinical and Economic Outcomes Associated With Use of Liposomal Bupivacaine Versus Standard of Care for Management of Postsurgical Pain in Pediatric Patients Undergoing Spine Surgery - Robert Tracy Ballock; John Seif; Ryan Goodwin; Jennifer H. Lin; Jessica Cirillo (Journal of Health Economics and Outcomes Research)
**Background:** Approximately 60% of hospitalized children undergoing surgery experience at least 1 day of moderate-to-severe pain after surgery. Pain following spine surgery may affect opioid exposure, length of stay (LOS), and costs in hospitalized pediatric patients. This is a retrospective cohort analysis of pediatric patients undergoing inpatient primary spine surgery.